2017
DOI: 10.1371/journal.pone.0178287
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography on the rocks: The contribution of current and historical factors in shaping the genetic structure of Chthamalus montagui (Crustacea, Cirripedia)

Abstract: The model marine broadcast-spawner barnacle Chthamalus montagui was investigated to understand its genetic structure and quantify levels of population divergence, and to make inference on historical demography in terms of time of divergence and changes in population size. We collected specimens from rocky shores of the north-east Atlantic Ocean (4 locations), Mediterranean Sea (8) and Black Sea (1). The 312 sequences 537 bp) of the mitochondrial cytochrome c oxidase I allowed to detect 130 haplotypes. High wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 57 publications
1
11
1
Order By: Relevance
“…Indeed, it was confirmed that the Almería-Orán Front acts on the population structure of several species as in P. elegans, e.g. the cuttlefish Sepia officinalis 40 , some fish species 41 , the barnacle Chthamalus montagui 42 or the wedge clam Donax trunculus 43 among others (see review in Patarnello et al 11 ). Notwithstanding, it is known that population connectivity across the Atlantic-Mediterranean transition is reduced in other species by different oceanographic discontinuities, namely the Strait of Gibraltar 24,44 , the Balearic Front and the Ibiza Channel 45,46 .…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, it was confirmed that the Almería-Orán Front acts on the population structure of several species as in P. elegans, e.g. the cuttlefish Sepia officinalis 40 , some fish species 41 , the barnacle Chthamalus montagui 42 or the wedge clam Donax trunculus 43 among others (see review in Patarnello et al 11 ). Notwithstanding, it is known that population connectivity across the Atlantic-Mediterranean transition is reduced in other species by different oceanographic discontinuities, namely the Strait of Gibraltar 24,44 , the Balearic Front and the Ibiza Channel 45,46 .…”
Section: Discussionmentioning
confidence: 90%
“…This remarkable pattern of genetic break, within the Eastern Mediterranean, has also been recorded in crustaceans. Notably, Shemesh et al [ 108 ] and later Pannacciulli et al [ 18 ] revealed marked genetic isolation in the barnacle species Chthamalus montagui between the western-central Mediterranean Sea and Aegean-Black seas. Gene flow restriction between western and eastern Mediterranean populations was shown to be mainly linked to the hydrographic isolation of the Aegean Sea, and found to be more marked than that associated with the Siculo-Tunisian Strait [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the phylogeography of Mediterranean species underwent a common set of processes resulting from fragmentation within glacial refugia, range expansions via postglacial colonisation, and secondary contact zones among historically divergent lineages [ 4 , 12 , 15 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the severe palaeogeographic and palaeoclimatic shifts that this region has undergone throughout its history, resulting in the onset of specific oceanographic features across its coastline, have set the stage for the impact of evolutionary and demographic processes on forging genetic variation of marine species [14, 17]. Recent phylogeographic investigations have provided evidence for the occurrence of pronounced genetic boundaries between the East Atlantic and the western Mediterranean, and between the Western and Eastern Mediterranean basins [2, 8, 15, 1822]. Further pronounced genetic breaks have also been documented in the eastern Mediterranean, notably between the Adriatic-Ionian seas and the Aegean-Marmara-Black seas [1, 8, 2226].…”
Section: Introductionmentioning
confidence: 99%
“…Recent phylogeographic investigations have provided evidence for the occurrence of pronounced genetic boundaries between the East Atlantic and the western Mediterranean, and between the Western and Eastern Mediterranean basins [2, 8, 15, 1822]. Further pronounced genetic breaks have also been documented in the eastern Mediterranean, notably between the Adriatic-Ionian seas and the Aegean-Marmara-Black seas [1, 8, 2226].…”
Section: Introductionmentioning
confidence: 99%